Biomimetic silica deposition promoted by sub-5 μm complexes of dicarboxylic acids/polyethyleneimine microballs: a new approach to tuning silica structures using messenger-like dicarboxylic acids. Issue 1 (20th December 2017) - Soma, Daiki; Jin, Ren-Hua
Abstract : Acid–base complexes prepared from sub-5 μm polyethyleneimine microballs and dicarboxylic acids promoted silica deposition to give silica microballs with different morphological surface structures which were controlled by the structures of the acids. Abstract : Acid–base complexes prepared from sub-5 μm polyethyleneimine (PEI) microballs and dicarboxylic acids such as adipic acid (AA), succinic acid (SA), meso -tartaric acid ( m -TA) as well as mucic acid (MA) were used as catalytic templates in hydrolytic condensation of tetramethoxy silane (TMOS). By means of FT-IR, 13 C NMR, 29 Si NMR, XRD, SEM, TGA and nitrogen sorption isotherms, we thoroughly investigated the effects of the dicarboxylic acids complexed with PEI microballs on the resultant silica structures. We found that in this silica deposition process, the presence of the dicarboxylic acids of adipic acid (AA) and succinic acid (SA), which do not have alcoholic groups, could adapt to deposit high content of silica than the alcoholic acids of meso -tartaric acid ( m -TA) and mucic acid (MA). More interestingly, the surface structures of the resultant silica microballs were different with different types of acids. The presence of m -TA and MA with meso -type alcoholic structures produced nanofibre or nanoplate-covered silica microballs, while the presence of AA and SA led to the formation of nanoparticles-covered silica microballs. Accompanying these structural features, the BET surface areas of the four types of acid-mediated silica microballs after calcination at 800 °C appeared remarkably different with the order of 615 > 430 > 133 > 96 m 2 g −1, respectively, corresponding to the contribution of MA, m -TA, SA and AA. These results evidently indicate that the structures of the dicarboxylic acids associated with PEI microballs play a messenger-like role to tune the silica structures.